Docking studies on novel analogs of quinolones against DNA gyrase of Escherichia coli - Cristian Davila; Lorena Llach; Guillermo Salgado-Moran; Rodrigo Ramirez-Tagle (GarVal Editorial Ltda., 2018)
Context: Bacterial resistance to antibiotics is the inevitable consequence of the use of antimicrobial agents. Thus, quinolones are an important class of antibacterials; these agents generally consist of a 1-subtituted-1,4-dihydro-4-oxopyridine-3-carboxylic acid moiety combined with an aromatic or heteroaromatic ring fused at the 5- and 6-position. Aims: To determine the binding of quinolones to DNA gyrase of Escherichia coli. Methods: An analysis was performed using an in silico approach to determine, by docking calculations and energy descriptors, the conformer of 4‐oxo‐1,4‐dihydroquinoline skeleton that forms the most stable complex with DNA gyrase of E. coli. Results: The complex shows that the pose of the quinolones coincides with the amino acid residues Asp87, Thr88, Arg91 and Met92, which is expected to be critical in the binding of quinolones to DNA gyrase of E. coli. A series of quinolones were computationally designed, and the interactions between the quinolones and the amino acid residues of the DNA gyrase were calculated. Conclusions: Among the designed compounds, compounds 105 and 115 exhibit higher binding energy values and interact with amino acids Asp87, Thr88, Arg91 and Met92.